Pengaruh Pendapatan, Pengetahuan, Promosi dan Harga Emas Terhadap Keputusan Mitra Bank Berinvestasi Emas di BSI Kota Jambi - Adry Rusdiansyah Meidi; Amri Amir; Nurida Isnaeni (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to analyze the influence of income, knowledge, promotion, and gold prices on the investment decisions of bank partners in investing in gold at Bank Syariah Indonesia (BSI) in Jambi City. The population used in this research consists of BSI partners who invest in gold in Jambi City, with a sample of 90 respondents. It can be concluded that the respondents in this study are predominantly female, totaling 63 respondents, while males amount to 27 respondents. Based on age, the majority are aged 30-39 years, with 40 respondents. In terms of education level, 70 respondents hold a bachelor's degree. Data collection techniques employed include questionnaires, documentation, and interviews. The data analysis method used is multiple linear regression analysis. The results show that all examined variables, both internal factors (income and knowledge) and external factors (promotion and gold prices), significantly influence gold investment decisions. The coefficient of determination (R²) of 0.827 indicates that 82% of the variation in the dependent variable can be explained by the variables studied. This research provides a broader understanding of the factors influencing gold investment decisions and suggests strategies for more effective promotion and better financial education.